Observations of pressure anisotropy effects within semi-collisional magnetized plasma bubbles - E. R. Tubman (Nature Portfolio, 2021)
Magnetic fields can be reorganized by plasma flows and lead to effects such as magnetic reconnection. Here the authors explore the evolution of magnetized-plasma bubbles in a semi-collisional regime and the role of pressure anisotropy in influencing the flow of the laser-produced plasma.